Analiza sektora MŚP na obszarze objętym Lokalnym Programem Rewitalizacji Zabłocia - Świerczewska-Pietras, Katarzyna (Przedsiębiorczość - Edukacja, 2009)
Local Revitalization Programs implemented by the Cities are to contribute to, among the otherfactors, activation and development of business activity. The programs constitute the strategyof the cities’ activities on post-industrial areas or those undergoing gradual degradation.According to the criteria listed in the Operational Programs developed by the Marshall Officesof particular province, local revitalization programs should include mechanisms supportingand activating the activities of small and medium enterprises. Thanks to the Local RevitalizationProgram adopted in October 2006, the Zabłocie area is to change its character from industrialone to that aimed to the development of the SME sector and its cultural and educationalfunctions.